The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.cmi.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Practical issues in implementing whole-genome-sequencing in routine diagnostic microbiology

Abstract: Background: Next generation sequencing (NGS) is increasingly being used in clinical microbiology. Like every new technology adopted in microbiology, the integration of NGS into clinical and routine workflows must be carefully managed. Aim: To review the practical aspects of implementing bacterial whole genome sequencing (WGS) in routine diagnostic laboratories. Sources: Review of the literature and expert opinion. Content: In this review, we discuss when and how to integrate whole genome sequencing (WGS) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
161
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(186 citation statements)
references
References 24 publications
2
161
0
2
Order By: Relevance
“…The ECDC study reported the requirement for sufficient bioinformatics expertise as one of the important hurdles to a more general implementation of NGS for routine testing 2 . This observation has also been expressed in recent case studies and reviews 711 .…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The ECDC study reported the requirement for sufficient bioinformatics expertise as one of the important hurdles to a more general implementation of NGS for routine testing 2 . This observation has also been expressed in recent case studies and reviews 711 .…”
Section: Introductionsupporting
confidence: 58%
“…This complex - and dynamic - reality poses a challenge for the implementation of bioinformatics pipelines in regulatory settings, where the demonstration of reliability and reproducibility is crucial (see also 11, 29). Harmonisation approaches must face the variability described above in terms of technologies, strategies, and software used, each with their demonstrated success, limitations and caveats.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome sequencing (WGS) is emerging as a routine clinical test that could be used to determine the bacterial species, undertake transmission tracking and identify multiple AMR associated mutations and genes in a single assay [8][9][10][11][12][13]. Whilst the initial clinical roll-out of WGS has used bacterial isolates, metagenomics and sequencing direct from clinical samples are future possibilities [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Typical workflow of genomic epidemiology may thus necessitate multiple colony picks per sample and the corresponding DNA library preparation and sequencing steps for each of them. Combined, these steps require a significant amount of laboratory effort and time, and lead to increased costs since the price of library preparation is becoming comparable to the cost of sequencing itself (Rossen et al 2018) . This can act as a barrier to more widespread genomic pathogen surveillance even in well-resourced public health laboratories, and prevent application of genomic epidemiology altogether in poorer settings.…”
Section: Introductionmentioning
confidence: 99%